Modulation of supramolecular self-assembly of BODIPY tectons via halogen bonding. Issue 36 (24th August 2021) - Özcan, Emrah; Dedeoglu, Burcu; Chumakov, Yurii; Zorlu, Yunus; Çoşut, Bünyemin; Ayhan, Mehmet Menaf
Abstract : In this study, the efficiency of halogen bonding strategies to control over the supramolecular assemblies of boron dipyrromethene (BODIPY) (B-1, B-2, and B-3 ) derivatives was explored. Abstract : In this study, the efficiency of halogen bonding strategies to control over the supramolecular assemblies of boron dipyrromethene (BODIPY) (B-1, B-2, and B-3 ) derivatives was explored. BODIPY cores were decorated with iodine (XB donor) and pyridine (XB acceptor) groups to promote halogen bonding formations. Single crystal X-ray diffraction analysis revealed the formation of I⋯X (N, F) XB, which led to the impressive halogen-bonded supramolecular self-assembly of 2-D layers (B-1 ), 1-D ladder-like chains (B-2 ), and helical assembly (B-3 ). The molecular electrostatic potential (MEP) showed the presence of σ holes on the outer tip of the iodine for all compounds. The SAPT analysis clarified the decomposition of interaction energies. The results revealed that the electrostatic forces have the largest contributions to XB in dimers of B-2, whereas dispersion components are the major source of XB interactions in dimers of B-1 and B-3 . The additional AIM theory analysis showed the bond critical points (BCPs) between I⋯N, F which also confirm the presence of halogen bonding in B-1, B-2, and B-3 .